Participation experiences and civic concepts, attitudes and engagement: implications for citizenship education projects - Isabel Menezes (2003)
This article considers participation experiences of 14 year-old and upper secondary students in six European countries that were involved in the International Association for the Evaluation of Educational Achievement (IEA) Civic Education Study: the Czech Republic, Norway, Portugal, Slovenia, Sweden and Switzerland, countries that vary in their history of institution of democratic regimes. Participation has been considered as a crucial dimension of citizenship, and experiences within civil society are viewed as a relevant opportunity for developing personal and social resources essential for the survival and expansion of democracy. Additionally, participation experiences in adolescence seem to be a good predictor of political engagement during adult life. Results show that participation is most evident in organisations that provide enrichment activities (sports, music, computers), but both 14 year-old and upper secondary students are involved in voluntary activities, in some civic-related organisations (mainly Scouts, religious affiliated and environmental), and in experiences within the school (with student councils and school newspapers at the top). However, cross-national and cross-age variations are significant. Overall, there seems to be a positive impact of the frequency of students' involvement on civic concepts, attitudes and engagement, but results also reveal that more is not necessarily better. The most relevant implication for the development of citizenship education projects is that 'action' can be a powerful learning tool but only if it is intentionally designed and systematically supported: the quality of participation experiences, both in terms of meaningful involvement, of interaction with (different) others, and opportunities for personal integration, is therefore crucial if the goal is to promote the personal empowerment and social pluralism on which the essence of democracy relies.